Relationship Between Preoperative Anemia and In-Hospital Mortality in Children Undergoing Noncardiac Surgery. (December 2016) - Faraoni, David; DiNardo, James A.; Goobie, Susan M.
Abstract : BACKGROUND: The relationship between preoperative anemia and in-hospital mortality has not been investigated in the pediatric surgical population. We hypothesized that children with preoperative anemia undergoing noncardiac surgery may have an increased risk of in-hospital mortality. METHODS: We identified all children between 1 and 18 years of age with a recorded preoperative hematocrit (HCT) in the 2012, 2013, and 2014 American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) pediatric databases. The endpoint was defined as the incidence of in-hospital mortality. Children with preoperative anemia were identified based on their preoperative HCT. Demographic and surgical characteristics, as well as comorbidities, were considered potential confounding variables in a multivariable logistic regression analysis. A sensitivity analysis was performed using propensity-matched analysis. RESULTS: Among the 183, 833 children included in the 2012, 2013, and 2014 ACS NSQIP database, 74, 508 had a preoperative HCT recorded (41%). After exclusion of all children <1 year of age (n = 12, 063), those with congenital heart disease (n = 8943), and those who received a preoperative red blood cell (RBC) transfusion (n = 1880), 12, 551 (24%) children were anemic, and 39, 071 (76%) were nonanemic. The median preoperative HCT was 33% (interquartile range, 31–35) in anemic children, and 39% (interquartile range, 37–42) in nonanemic children ( P < .001). Using multivariable logistic regression analysis, and after adjustment for RBC transfusion (OR, 2.13; 95% CI, 1.39–3.26; P < .001), we observed that preoperative anemia was associated with higher odds for in-hospital mortality (OR, 2.17; 95% CI, 1.48–3.19; P < .001). After propensity matching, the presence of anemia was also associated with higher odds of in-hospital mortality (OR, 1.75; 95% CI, 1.15–2.65; P = .004). CONCLUSIONS: Our study demonstrates that children with preoperative anemia are at increased risk for in-hospital mortality. Further studies are needed to assess whether the correction of preoperative HCT, through the development of a patient blood management program, improves patient outcomes or simply reduces the need for transfusions.